Threshold Effect of Intelligence in the FDI-Growth Nexus - Nurshila Ahmad; Muhammad Daaniyall Abd Rahman; W.N.W. Azman-Saini; Yasmin Bani; Anitha Rosland (The Publisher, 2025)
This paper examines whether there is a threshold effect of intelligence in the relationship between FDI and economic growth. It proposes that only countries with a sufficiently high level of intelligence can gain from FDI inflows. To test this, the study uses data from 85 countries covering the period 1976–2018. A threshold regression model is applied to capture the non-linear impact of FDI on growth. The results show that FDI contributes positively to growth only after a country reaches a certain level of intelligence. Below this threshold, FDI has no significant effect on growth.